Influential Aspects of Knowledge Sharing in the Context of a Marketplace Platfrm During the COVID-19 Pandemic: A Brazilan Case Study - Bitencourt Jorge, Carlos Francisco [UNESP]; de Camargo Ferraz Machado, João Guilherme [UNESP]; Martins Menegassi, Cláudia Herrero; da Silva Stecca, Rodrigo [UNESP]; Sutton, Michael J. D. (World Scientific Publishing, 2023)
The COVID-19 pandemic and social distancing entangled physical trading of products and services worldwide. As a result, the Commercial and Industrial Association of Marília (ACIM) developed and provided businesses with a marketplace platform called “Marília.Dakki.” In this context, knowledge emerged as a resource, and knowledge sharing became a fundamental activity for the marketplace implementation. Thus, the objective of the research was to identify and analyze the influential aspects of knowledge sharing (IAKS) in “Marília.Dakki.” The research is characterized as qualitative and exploratory and used the case study method. Questionnaires were used to acquire data from the 19 subjects involved in the “Marília.Dakki” operations, as well as an interview with the Director of IT and Innovation. As a result of the research, people, processes, and culture were identified as IAKS, and these aspects, when related, generated nine other IAKS. The researchers concluded that these IAKS found in the research impacted the marketplace adoption, in addition to its maintenance as a collaborative environment, and are of great importance for the survival and development of companies, both during the pandemic and after it.
Keywords: Commercial and Industrial Association of Marilia; COVID-19; Knowledge Sharing; Marketplace; Online Sales